Culture, Criminality and Violence in The Nsukka Area of Enugu State, in 21st Century - Egbuniwe, Ozioko Peter; Onyenaezichi, Odoh Samuel; Ebu, Solomon Ososhepoh; Victor O, Akalonu (South Asian Journal of Social Sciences and Humanities, 2021)
Globally, culture is a universal phenomenon which distinguishes a particular race, tribe ethnic group from one another. The culture of a people defines them. People’s culture is exhibited through masquerade, music, art works, dance, building patterns, marriage among others. In Igboland and Nsukka areas in particular the people’s cultural exhibition is annually showcased mainly through masquerade such as Akatakpa, Oriokpa, Omabe, Odo, Ogede amongst others. However, criminality and violence have crept into the cultural exhibitions of the people of Nsukka and opinions are divided among the different stakeholders in the society on the appropriate measure to curb this menace of masquerade in the name of cultural exhibitions. The thrust of this chapter is to interrogate the correlations between cultural exhibitions, criminality and violence in Nsukka areas during their annual masquerade fiesta in this 21st century, Nigeria. The chapter also adopts qualitative research methodology and makes use of both primary and secondary sources such as relevant books, institutional publications, oral interviews among others. It was discovered in the course of the research that criminalities and violence perpetrated by the masquerades are not intractable and could be stamped out through a concerted effort of all the stakeholders in Nsukka.